Cambridge preliminary English test 4 with ansers: Examination papers from university of Cambridge ESOL examinations English for speaker of other language - Cambridge University (Cambridge University, 2013)
Hướng dẫn người học cách chuẩn bị kỳ thi PET. Cung cấp 4 bài kiểm tra đề thi PET, mỗi bài bao gồm: Nghe, Nói, Đọc, Viết. Kèm theo đáp án và tapescript.